PENGEMBANGAN BAHAN AJAR TEMATIK TERPADU BERBASIS VALUE CLARIFICATION TECHNIQUE (VCT) EXAMPLE DI KELAS V SD - Isra Dumiati Ermon; Reinita Reinita (JURNAL HANDAYANI PGSD FIP UNIMED, 2021)
Abstract: Development of Integrated Thematic Teaching Materials Based on Value Clarification Technique (VCT) Example in Class V SD was conducted at SDN 33 Sawahan because at that school the learning resource books were still relatively small. The teacher has never used the VCT Example model in learning. This study aims to determine the validity and practicality of the product. This type of research is R&D, using a 4-D development model. The subjects of this study were 3 experts and 1 grade V teacher and 22 grade V students at SDN 33 Sawahan. The questionnaires used is validation sheets, teacher and student response questionnaires. The dissemination stage was carried out after a trial at SDN 33 Sawahan. This distribution stage also uses a practicality questionnaire with the response of 1 class V teacher and the response of 27 class V students.The results of the study of teaching materials developed showed:(1) Integrated Thematic Teaching Materials Based on the VCT Example in Class V SD was declared very valid with an average score of 88% of teaching materials experts, 88% of material experts and 93% of linguists ( 2) student and teacher responses to the VCT Example Integrated Thematic Teaching Materials in Class V SD obtained a practical category with an average value of student responses of 85.22% and teacher responses of 95%. (3) The distribution carried out obtained the results of student and teacher responses to the developed product with an average value of 83.70% student response and 95% teacher response. Keywords: Teaching Materials, Value Clarification Technique, Example Abstrak:Pengembangan Bahan Ajar Tematik Terpadu Berbasis Value Clarification Technique (VCT) Example di Kelas V SD dilakukan di SDN 33 Sawahan karena pada sekolah tersebut buku sumber pembelajaran masih tergolong sedikit. Guru belum pernah menggunakan model VCT Example dalam melakukan pembelajaran. Penelitian ini bertujuan untuk mengetahui validitas dan praktikalitas produk. Jenis penelitian ini adalah R&D dengan menggunakan model pengembangan 4-D. Subjek dari penelitian ini yaitu 3 orang ahli dan 1 guru kelas V serta 22 peserta didik kelas V SDN 33 Sawahan. angket yang digunakan antara lain lembar validasi ahli, angket respon guru dan peserta didik. Tahap peneyebaran dilakukan setelah dilakukannya uji coba di SDN 33 Sawahan. Tahap penyebaran ini juga menggunakan angket praktikalitas dengan respon 1 guru kelas V dan respon 27 peserta didik kelas V. Hasil penelitian bahan ajar yang dikembangkan menunjukkan: (1) Bahan Ajar Tematik Terpadu VCT Example di Kelas V SD dinyatakan sangat valid dengan nilai rata rata ahli bahan ajar 88% , ahli materi 88% dan ahli bahasa 93% (2) respon siswa dan guru terhadap Bahan Ajar Tematik Terpadu Berbasis VCT Example di Kelas V SD memperoleh kategori praktis dengan nilai rata rata dari respon siswa 85,22 % dan respon guru 95%. (3) penyebaran yang dilakukan memperoleh hasil respon peserta didik dan guru terhadap produk yang dikembangkan dengan nilai rata rata respon siswa 83,70% dan respon guru 95% Kata Kunci: Bahan Ajar, Teknik Klarifikasi Nilai, Percontohan